An Updated Review on Pharmacology and Toxicities Related to Chloramphenicol - Singhal, Kanti Kumar; Mukim, MD; Dubey, Chetan Kumar; Nagar, Jagdish Chandra (Asian Journal of Pharmaceutical Research and Development, 2020)
Chloramphenicol is a antimicrobial drug primarily its bacteriostatic, though at high concentration it shows bactericidal actions on some bacteria e.g. H. Influenzae. Initially chloramphenicol is obtained from sterptomycesvenezuelae in 1947, now its synthesized chemically and all the commercial product is synthetic. Chloramphenicol displays a broad-spectrum bacteriostatic activity by specifically inhibiting the bacterial proteinsynthesis. In certain but important cases, it also exhibits bactericidal activity, namely against thethree most common causes of meningitis, Haemophilusinfluenzae, Streptococcus pneumoniae andNeisseria meningitidis. Resistance to Chloramphenicol has been frequently reported and ascribed to a variety ofmechanisms. However, the most important concerns that limit its clinical utility relate to side effectssuch as neurotoxicity and hematologic disorders. In this review, we present previous and current research on Chloramphenicol and its derivatives with improved pharmacological properties.